Developing Creativity Through Creative Engagement in Art Appreciation: Outcomes in Teaching Humanities - Alimen, Ma Cecilia; Poral, Pinky Jasmin; Magpantay, Rhounella Rhane; Quiros, Rosella; Azarcon, Ma Elena (International Journal of Language and Literary Studies, 2021)
This descriptive-correlational study determined the level of creative engagement as part of humanities teaching in the outcome-based education. This focuses on the dimension of student engagement and creativity in the context of a new approach to teaching and learning primarily through the arts. This study captures student creative engagement supported by their personal reflection after the course term. There were eight (8) classes utilized with 134 students. Results showed that the level of students’ creativity in art appreciation was “high” and it was also “high” when they were grouped as to sex. Creative engagement in art appreciation was considered “highly influential” and it was “highly influential” when they were grouped as to sex. No significant difference was noted in the level of the students’ creative engagement and development of creativity. There was a moderate and positive correlation between the level of the students’ creative engagement and influence of creative engagement in art appreciation classes to their development of creativity. The most highly valued creative engagement practices of students in art appreciation are: “I have developed an appreciation for the local arts;” “I have deepened my sensitivity of myself, my community and the society,” and “Inclusion of art activities demonstrated my understanding of art appreciation.